Primary-Role Academic Advising Professional Socialization/Identity - McGill, Craig M.; Puroway, Drew; Duslak, Mark (My University, 2020)
The following reflection protocol was developed by Craig M. McGill, Drew Puroway and Mark Duslak for the purpose of exploring our socialization to the emerging profession of academic advising. Collaborative autoethnography (CAE) is a research method in which a group of individuals draw upon their own lives and experiences to explore an issue. In CAE, therefore, the researchers are also the participants.
Keywords: Collaborative autoethnography; Critical reflection; Higher education; Researcher-participant; Professional socialization